2022
DOI: 10.48550/arxiv.2201.02252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New binary black hole mergers in the LIGO--Virgo O3a data

Abstract: We report the detection of ten new binary black hole (BBH) merger signals in the publicly released data from the the first half of the third observing run (O3a) of advanced LIGO and advanced Virgo. Candidates are identified using an updated version of the search pipeline described in Venumadhav et al.[1] (the "IAS pipeline" [2]), and events are declared according to criteria similar to those in the GWTC-2.1 catalog [3]. The updated search is sensitive to a larger region of parameter space, applies a template p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 131 publications
1
32
0
Order By: Relevance
“…Very recently, Olsen et al (2022) reported an marginal candidate, GW190920 113516, whose secondary could be a heavy NS. With an effective inspiral spin of χ eff = 0.60 +0.26 −0.07 , this event could be a potential NSBH merger with the NS first born.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Very recently, Olsen et al (2022) reported an marginal candidate, GW190920 113516, whose secondary could be a heavy NS. With an effective inspiral spin of χ eff = 0.60 +0.26 −0.07 , this event could be a potential NSBH merger with the NS first born.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We focus on the findings from LVK. Independent groups have reproduced these results and found additional events[48][49][50].…”
mentioning
confidence: 65%
“…Gravitational waves are now regularly observed by the ground-based observatories Advanced LIGO [1] and Advanced Virgo [2]. Their accomplishments include more than 90 observed binary black hole (BBH) mergers [3][4][5] and a handful of binary neutron star [6,7] and neutron star -black hole mergers [8]. These observations provide a wealth of knowledge for understanding the population of stellar-mass black holes [9], which may have arisen through standard stellar evolution [10].…”
Section: Introductionmentioning
confidence: 99%